A beautiful blue death - Finch, Charles (Charles B.) (Finch, Charles (Charles B.) Charles Lenox series, 2017)
When a servant girl is found dead, a supposed suicide, Victorian gentleman and amateur sleuth Charles Lenox is called in by his old friend, Lady Jane, to investigate and begins to suspect that the girl has fallen victim to a rare and deadly poison.